Telomere length is reset during early mammalian embryogenesis - Schaetzlein, Sonja (National Academy of Sciences, 2004)
The enzyme telomerase is active in germ cells and early embryonic development and is crucial for the maintenance of telomere length. Whereas the different length of telomeres in germ cells and somatic cells is well documented, information on telomere length regulation during embryogenesis is lacking. In this study, we demonstrate a telomere elongation program at the transition from morula to blastocyst in mice and cattle that establishes a specific telomere length set point during embryogenesis. We show that this process restores telomeres in cloned embryos derived from fibroblasts, regardless of the telomere length of donor nuclei, and that telomere elongation at this stage of embryogenesis is telomerase-dependent because it is abrogated in telomerase-deficient mice. These data demonstrate that early mammalian embryos have a telomerase-dependent genetic program that elongates telomeres to a defined length, possibly required to ensure sufficient telomere reserves for species integrity.